2012
DOI: 10.1371/journal.pone.0030295
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Assessment of Asp Isomerization and Asn Deamidation in Recombinant Antibodies by LC-MS following Incubation at Elevated Temperatures

Abstract: The degradation of proteins by asparagine deamidation and aspartate isomerization is one of several chemical degradation pathways for recombinant antibodies. In this study, we have identified two solvent accessible degradation sites (light chain aspartate-56 and heavy chain aspartate-99/101) in the complementary-determining regions of a recombinant IgG1 antibody susceptible to isomerization under elevated temperature conditions. For both hot-spots, the degree of isomerization was found to be significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 29 publications
8
100
1
Order By: Relevance
“…These studies have reported loss of stability, activity of proteins, and also increased aggregation properties as shown in crystallins, 7,8,11,12,23,24,[51][52][53] superoxide dismutase, 49 and immunoglobins. 14,34,54 Reported properties of mutC suggest that this protein has retained the secondary and tertiary structure with a partial loss in activity but with a significant improvement in the ability to withstand multiple heat cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have reported loss of stability, activity of proteins, and also increased aggregation properties as shown in crystallins, 7,8,11,12,23,24,[51][52][53] superoxide dismutase, 49 and immunoglobins. 14,34,54 Reported properties of mutC suggest that this protein has retained the secondary and tertiary structure with a partial loss in activity but with a significant improvement in the ability to withstand multiple heat cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Modified work flows are being developed to avoid process-induced deamidation. [34][35][36] In the case of 6B, incubation at 37 C during proteolysis did not result in deamidation, and reduction step is not required as 6B lipase does not have a cysteine. Most of the proteomic methods use electrospray ionization in combination with electron capture dissociation 37 or electron transfer dissociation 38 for qualitative determination of the product type, that is, aspartate or isoaspartate.…”
Section: Temperature-induced Deamidation and Loss Of Activity In Lipamentioning
confidence: 97%
“…A common mAb PTM is Nglycosylation at Asn 297 of the CH2 region, resulting in considerable proteoform heterogeneity from the combination of glycans at the two glycosylation sites [14]. Other PTMs, further increasing proteoform heterogeneity, include Met 1 -loss, formation of pyroglutamic acid, Cterminal lysine clipping, carboxymethylation of lysine, oxidation, deamidation, disulfide bond formation, glycation, single site amino acid replacement, and sequence truncation, amongst others [13,[15][16][17][18] . .…”
Section: Proteins As Pharmaceuticalsmentioning
confidence: 99%
“…After administration, the accumulated succinimide hydrolyzes to Asp and/or isoAsp under the physiologic pH. In mAbs, deamidation has been reported in the Fc regions [4,5] and the CDRs [6][7][8][9][10][11][12]. Deamidation in the CDR regions could affect drug efficacy [10,12].…”
Section: In Vivo Mab Modificationsmentioning
confidence: 99%